Tyche and Mount Argaeus on some autonomous civic bronzes of Eusebeia, Cappadocia - Bliss, Alex (KOINON: The International Journal of Classical Numismatic Studies, 2025)
As has been previously described by a number of scholars, the Cappadocian city of Mazaca (modern Kayseri, Turkey) was renamed Eusebeia around the mid-2nd century BC in honour of King Ariarathes V Eusebes Philopator. Sacked in 77 BC during the Mithridatic Wars, it subsequently lay abandoned for approximately a decade. Rebuilding and restoration undertaken by the Roman statesman Pompey from 67 BC onwards seems to have stimulated a reversal in its fortunes, the return of previously exiled citizens being promptly followed by an enthusiastic emission of civic coinage.